MENUMBUHKAN MINAT MENABUNG SEJAK DINI DI NAGARI KOTO ANAU TAPAN - Mua'rif, Zul Ihsan; Bustami, Alek Wissalam; Mailindra, Wiyan; Novita, Nina Delvia; Rahmah, Sopia (Institut Agama Islam Negeri Kerinci, 2024)
This article presents a community engagement effort in Nagari Koto Anau Tapan aimed at fostering an early interest in saving from the perspective of Islamic Economics. Saving is a crucial aspect of building financial stability for individuals, families, and communities, especially within Islamic values. Through socialization, education, and guidance activities, this program seeks to enhance understanding and awareness among the community, particularly elementary school children, about the importance of saving and responsible financial management. Program activities include the delivery of material on the concept of saving in Islam, presenting the benefits of saving in daily life, and establishing sustainable saving habits. Through a holistic and inclusive approach, it is hoped that the community in Nagari Koto Anau Tapan can gain a deeper understanding of sustainable saving practices in line with the principles of Islamic Economics. Thus, this article provides an overview of concrete efforts to build financial awareness and sustainable saving habits within the local community and the importance of integrating Islamic values into personal and family financial management.